The yield of monitoring adenovirus in pediatric hematopoietic stem cell transplant patients. (3rd April 2019) - Ali, Salah; Krueger, Joerg; Richardson, Susan E.; Sung, Lillian; Waespe, Nicolas; Renzi, Samuele; Chiang, Ky; Allen, Upton; Ali, Muhammad; Schechter, Tal
Abstract: Human adenovirus (HAdV) is recognized as a serious pathogen after allogeneic hematopoietic stem cell transplantation (HSCT), causing morbidity and mortality. Currently, there is no universal agreement regarding routine HAdV surveillance after HSCT. We assessed the impact of HAdV weekly monitoring by polymerase chain reaction (PCR) on HAdV viremia rates and the risk factors that influence survival. Three-hundred and fifty-six pediatric allogeneic HSCT were done between 2007 and 2015. Until July 2011, HAdV testing was performed based on clinical suspicion (cohort 1, n = 175) and from August 2011, weekly blood-HAdV monitoring was done (cohort 2, n = 181) until day +100. Twenty-three patients (4 [2.3%] from cohort 1 and 19 [10.5%] from cohort 2, p = .001) were found with HAdV viremia and seven of them died. Both cohorts had a similar incidence of HAdV-associated mortality (3/175; 1.7% in cohort 1 and 4/181; 2.2% in cohort 2). Respiratory failure was the cause of death in all patients. Clinical symptoms appeared prior to or within 5 days of HAdV detection in cohort 2. In summary, weekly monitoring was associated with higher detection of HAdV. The study could not assess survival benefit due to small numbers of HAdV-positive cases. In many instances, symptoms occurred with the development of positive HAdV blood PCR results and hence, symptomatology could have triggered the test. Future studies are needed to provide data that help establishing a uniform approach for regular monitoring of HAdV post-transplant.